EVALUATION OF THE ANALGESIC ACTIVITY OF AQUEOUS AND ALCOHOLIC EXTRACT OF FLOWERS OF PLUMERIA ALBA LINN IN EXPERIMENTAL ANIMALS - VINOTHA AT, SATHIYA; MS, UMAMAGESWARI; A, UMAMAHESWARI; S, VELARUL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Plumeria alba (Apocynaceae), commonly known as “Frangipani” is an important medicinal plant, widely distributed throughout Southern India. In the traditional medicinal system, different parts of this plant have been mentioned to be useful in a wide variety of diseases. In this study, analgesic activity of aqueous and alcoholic extract of flowers of P. alba Linn was evaluated by hot-plate and acetic acid-induced writhing methods to substantiate and expand its clinical applications. Methods: The flowers of P. alba were collected from the local area in and around Coimbatore (India). The flowers were dried, powdered, and were extracted using soxhlet apparatus for 12 h using water and 95% of ethanol as a solvent. The test extracts were administered orally at a dose of 100 and 200 mg/kg while diclofenac sodium (10 mg/kg) served as standard. Results: The ethanolic flower extract of 200 mg/kg had significant analgesic activity in acetic acid-induced abdominal writhing response (***p<0.001) when compared to control and standard drug diclofenac. It also exhibited significant analgesic activity (***p<0.001) by increasing the pain reaction time of the rats in comparison to control and standard in hot plate method. Conclusion: The results suggest that ethanolic flower extracts of P. alba possess potent analgesic properties, which support its use in traditional medicine and suggesting that the plant should be further investigated for its pharmacological active natural products.